2017
DOI: 10.1523/jneurosci.0933-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Contributions to Stimulus–Reward Encoding in the Macaque Medial and Orbital Frontal Cortex during Learning

Abstract: Orbitofrontal cortex (OFC), medial frontal cortex (MFC), and amygdala mediate stimulus-reward learning, but the mechanisms through which they interact are unclear. Here, we investigated how neurons in macaque OFC and MFC signaled rewards and the stimuli that predicted them during learning with and without amygdala input. Macaques performed a task that required them to evaluate two stimuli and then choose one to receive the reward associated with that option. Four main findings emerged. First, amygdala lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 48 publications
7
60
0
Order By: Relevance
“…Lesions of the OFC lead to severe deficits when stimulusoutcome contingencies need to be updated (Jones and Mishkin 1972;Dias et al 1996;Izquierdo et al 2004;Walton et al 2010). Although recent work with selective excitotoxic lesions of the OFC in macaques (Rudebeck et al 2013) has overturned the idea that the OFC is necessary for learning reversals of stimulus-reward contingencies-at least in deterministic settings-recordings from single neurons have shown that OFC neurons change their activity to visual stimuli when the type of their associated outcome changes (Thorpe et al 1983;Rolls et al 1996;Morrison et al 2011) and during learning (Wallis and Miller 2003;Rudebeck et al 2017). Taken together, these results suggest the OFC plays an important role in tracking stimulusreward associations.…”
mentioning
confidence: 98%
“…Lesions of the OFC lead to severe deficits when stimulusoutcome contingencies need to be updated (Jones and Mishkin 1972;Dias et al 1996;Izquierdo et al 2004;Walton et al 2010). Although recent work with selective excitotoxic lesions of the OFC in macaques (Rudebeck et al 2013) has overturned the idea that the OFC is necessary for learning reversals of stimulus-reward contingencies-at least in deterministic settings-recordings from single neurons have shown that OFC neurons change their activity to visual stimuli when the type of their associated outcome changes (Thorpe et al 1983;Rolls et al 1996;Morrison et al 2011) and during learning (Wallis and Miller 2003;Rudebeck et al 2017). Taken together, these results suggest the OFC plays an important role in tracking stimulusreward associations.…”
mentioning
confidence: 98%
“…Many studies have shown that the OFC is important for dynamically updating and tracking stimulus-value association (Morrison et al, 2011;Rolls et al, 1996;Rudebeck et al, 2008Rudebeck et al, , 2017Thorpe et al, 1983). Here we showed that the OFC did not integrate and update value information during decision making.…”
Section: Ofc and Valuementioning
confidence: 54%
“…This aids the 374 interpretation of the results; if there had been a behavioral deficit postoperatively it would be 375 difficult to interpret any postoperative changes in neural activity, as effects could be due to 376 either the lesion or the change in behavior. In addition, we confirmed that the lesions were 377 effective in a separate task that required the learning of new stimulus-reward associations 378 (Rudebeck et al, 2017). 379…”
Section: Task and Behavioral Performance 362mentioning
confidence: 58%
“…By contrast, if the value of stimuli changed unexpectedly or has to be learned, 881 this might trigger a cascade of events throughout the PFC, increasing the need for cognitive 882 control which could potentiate the processing of choice and value information in the MFC and 883 OFC, respectively. This idea would appear to fit with data from the same subjects showing that 884 during stimulus-reward learning, single neuron activity in MFC closely matches stimulus values 885 and is indistinguishable from OFC encoding (Rudebeck et al, 2017). 886 887…”
Section: Correspondence Between Erps and Single Neuron Activity 848mentioning
confidence: 71%